Evaluation of Growth Performances and Meat Quality of Tunisian Local Poultry Raised in Outdoor Access - Raach-Moujahed, A.; Haddad, B.; Moujahed, N.; Bouallegue, M. (International Journal of Poultry Science, 2011)
Local and indigenous poultry in Tunisia represent very diversified and heterogeneous populations which remain largely unknown and understudied in spite of the real economic assets that they seemed to represent mainly in rural areas. The present study was envisaged in the objective of conservation, valorization and development of this rustic and well adapted genetic substrate. In this respect growth parameters were measured and meat quality measurements on pH and color (L*: luminance, a*: yellowness b*: redness) were operated. Results showed that a mean Body Weight (BW) of 632 g was reached at week 8, 923 g at week 12 and 1249 g at week 16, with mean Daily Weight Gain (DWG) of 16.72, 11.26 and 10.89 g/d respectively. Males were found to be more (p